2007
DOI: 10.1038/nature06010
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies KIAA0350 as a type 1 diabetes gene

Abstract: Type 1 diabetes (T1D) in children results from autoimmune destruction of pancreatic beta cells, leading to insufficient production of insulin. A number of genetic determinants of T1D have already been established through candidate gene studies, primarily within the major histocompatibility complex but also within other loci. To identify new genetic factors that increase the risk of T1D, we performed a genome-wide association study in a large paediatric cohort of European descent. In addition to confirming prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
389
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 485 publications
(410 citation statements)
references
References 32 publications
15
389
1
2
Order By: Relevance
“…2,6,8,11 The most significantly associated SNP, rs12923849 has previously showed some degree of association with T1D. 1 The other three top hits in our screening phase; rs9934231, rs6498168 and rs7206912 have not previously been reported to be associated in MS or other autoimmune diseases. Because of failure of genotyping rs6498168 in the replication phase, it was replaced by a SNP in complete LD (r 2 ¼ 1), rs8060411, and this SNP was for completeness, also tested in the screening panel.…”
Section: Screening Phasementioning
confidence: 83%
See 3 more Smart Citations
“…2,6,8,11 The most significantly associated SNP, rs12923849 has previously showed some degree of association with T1D. 1 The other three top hits in our screening phase; rs9934231, rs6498168 and rs7206912 have not previously been reported to be associated in MS or other autoimmune diseases. Because of failure of genotyping rs6498168 in the replication phase, it was replaced by a SNP in complete LD (r 2 ¼ 1), rs8060411, and this SNP was for completeness, also tested in the screening panel.…”
Section: Screening Phasementioning
confidence: 83%
“…Thus, they cluster in some proximity to regions where differences are seen in the transcripts. Hakonarson et al 1 have previously studied CLEC16A expression in NK cells in view of the T1D-associated SNP rs2903692 and found that homozygotes for the A allele showed a trend towards increased CLEC16A mRNA expression (KIAA0350/CLEC16A Affymetrix probe set 231221 (Affymetrix, Santa Clara, CA, USA) ). Interestingly, this SNP rs2903692 is in strong LD (r 2 ¼ 0.88) with rs12708716.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genotypes in the parents were in Hardy-Weinberg equilibrium with P ¼ 0.410. The remaining SNPs in the panel were chosen to follow-up the first stage of a genome-wide association study 4 . The transmission disequilibrium test (TDT) and the conditional logistic regression analysis were done using the TDTPHASE program in the UNPHASED software (http://www.hgmp.mrc.ac.uk/Bfdudbrid/ software/unphased/).…”
Section: Resultsmentioning
confidence: 99%